Anti-Helicobacter pylori activity and immunostimulatory effect of extracts from Byrsonima crassa Nied. (Malpighiaceae) - Vilegas Wagner; Sannomiya Miriam; Carlos Iracilda Z; Raddi Maria; Bonacorsi Cibele (BMC, 2009)
Abstract Background Several in vitro studies have looked at the effect of medicinal plant extracts against Helicobacter pylori (H. pylori). Regardless of the popular use of Byrsonima crassa (B. crassa) as antiemetic, diuretic, febrifuge, to treat diarrhea, gastritis and ulcers, there is no data on its effects against H. pylori. In this study, we evaluated the anti-H. pylori of B. crassa leaves extracts and its effects on reactive oxygen/nitrogen intermediates induction by murine peritoneal macrophages. Methods The minimal inhibitory concentration (MIC) was determined by broth microdilution method and the production of hydrogen peroxide (H2O2) and nitric oxide (NO) by the horseradish peroxidase-dependent oxidation of phenol red and Griess reaction, respectively. Results The methanolic (MeOH) and chloroformic (CHCl3) extracts inhibit, in vitro, the growth of H. pylori with MIC value of 1024 μg/ml. The MeOH extract induced the production H2O2 and NO, but CHCl3 extract only NO. Conclusion Based in our results, B. crassa can be considered a source of compounds with anti-H. pylori activity, but its use should be done with caution in treatment of the gastritis and peptic ulcers, since the reactive oxygen/nitrogen intermediates are involved in the pathogenesis of gastric mucosal injury induced by ulcerogenic agents and H. pylori infections.